A longitudinal transitional perspective on why adolescents choose to quit organized sport in Norway. (September 2021) - Bentzen, Marte; Hordvik, Mats; Stenersen, Magne Hem; Solstad, Bård Erlend
Abstract: The present study used a prospective cohort design to explore the reasons why young athletes decided to quit playing handball. The theoretical underpinnings were drawn from the fields of career transition, motivation, and meaningful experiences in organized youth sport. Thirty-four athletes were included in a larger research project exploring the complex interplay of psychosocial factors during the transition period from lower-to upper-secondary school in Norway. In this study, the data collection involved three sources: individual interviews with the 10 athletes who decided to leave their teams during the study period (five girls and five boys), and individual open-ended questionnaires for these 10 participants collected five times over two seasons, aligned with their participation in focus group interviews. The data analysis involved a three-step process of inductive content analysis of the total corpus of the data. A core finding indicates that all adolescents had gone through a decision-making process over time to determine whether they should continue or quit. It was a process of accumulating reasons that resulted in the final decision. However, the results reveal a broad variation within individual perception and interpretation of what each adolescent experienced as meaningful. Of equal importance, the adolescents not only took their experiences in sport into account when considering quitting organized youth sport, but these were considered in light of their evaluation of meaningfulness in other areas of life. Overall, findings indicate that "dropping out of organized youth sport" should not be regarded as unambiguously negative. Highlights: This prospective study explored reasons why adolescents decide to quit sport. The transition period from lower-secondary to upper-secondary school was targeted. The decision to quit was a result of evaluation over time with accumulating reasons. Reasons to quit were related to experiences of meaningfulness in and outside sport. The adolescents chose to quit sport in favor of other meaningful activities in life.